Hotel pioneers' leadership styles: A case study on the founders of Oberoi Group and Soneva and Six Senses Resort and Spa - Manisa Piuchan (2020)
© 2019 Institute for Tourism. All rights reserved. This study aimed to demonstrate the leadership characteristics and styles of two leading hotel operators in Asia. It was based on a biographical research technique using secondary data. Content analysis was employed to identify the leadership styles and key characteristics of the selected leaders. The major discussions in this work are separated into two parts. The backgrounds and leadership styles of each hotel operator are discussed in the fi rst part. Results indicated that Sonu Shivdasani, the founder of Soneva and Six Senses Resort and Spa, demonstrated transformational leadership style. By contrast, Mohan Singh Oberoi, the founder of Oberoi Group, exhibited transformational and charismatic leadership. Four commonly shared characteristics on how to be successful hotel leaders are discussed in the second part of the study. The identifi ed characteristics include visionary leadership, charismatic leadership, entrepreneurial leadership and ethical leadership. The study provided supporting information and identifi ed characteristics from the life story, personalities and professional career success of the two hotel operators. Discussions and results could improve our understanding of the styles and shared characters underlying the success of these operators, which will be specifi cally useful for the development of hotel leadership.